Propuesta de una guía turística virtual para los museos de la ciudad de Loja. - Medina Torres, Rotseli Nicol (2023)
The present work was titled "Proposal for a virtual tourist guide for museums of Loja city". The general objective was to propose the design of a virtual tourist guide in museums of Loja city; being an innovative alternative for the promotion and dissemination of the museums of the city of Loja, which are Cultural Heritage and jealously guard the history of the city, in addition, said proposal may generate greater tourist influx and economic reactivation within the city. Likewise, three specific objectives were set up: the first, to diagnose the current situation of Loja city’s museums, the second, to design a virtual tourist guide of Loja’s museums, and the third, to develop a communication plan for the promotion and diffusion of the virtual tourist guide of Loja’s museums.Regarding to the methodology, the following methods were used: descriptive, inductive, deductive, analytical and explorative; techniques such as direct observation, interviews, surveys and sample size. In the same way, it was used Carla Ricaurte’s adapted methodology, taking into account the indicators of INPC and MINTUR files. As a result of this work, it is the creation of a web page with the tourist guide on video format. The prioritized information is found on the web page according to the results of the surveys and interviews. Finally, it was possible to conclude that museums of Loja city have patrimonial wealth that must be seen not only locally but also nationally and internationally. In addition, recommendations were generated for the coordinators of each museum, who must work as a team to create cultural touristic routes.